Vastus lateralis versus rectus femoris muscle flaps for recalcitrant hip joint infection: An anatomical study comparing the effectiveness of acetabular dead space control. Issue 7 (2nd July 2022) - Smith, Alexandria H.; Brassett, Cecilia; Gooding, Christopher; Abood, Ahid; Norrish, Alan
Abstract: Eliminating recalcitrant prosthetic hip joint infections remains one of the greatest challenges in orthopedic surgery. In such cases, the salvage procedure of femoral head excision (the Girdlestone procedure) is often performed. There has been emerging surgical interest in filling the resulting acetabular dead space with a pedicled muscle flap, to enable antibiotic delivery. Both vastus lateralis (VL) and rectus femoris (RF) muscle flaps have been described for this purpose with good success. This study is the first anatomical investigation comparing VL and RF as candidates for interposition myoplasty following hip joint excision. Following standard surgical technique, the Girdlestone procedure and interposition myoplasty of both RF and VL were performed on 10 cadavers. The primary aim was to determine which muscle flap eliminated a greater volume of acetabular dead space. Secondary aims were to characterize the blood supply to RF and assess additional metrics indicative of the likelihood of flap success. The VL flap eliminated more dead space than RF. However, the use of the RF flap was feasible in all cases and has several benefits, including ease of harvest, mobility, and aesthetics. The location of the inferior vascular pedicle into RF was relatively consistent and the most effective predictor of flap success. Both VL and RF are effective in reducing acetabular dead space. While VL can fill a greater volume, the RF flap has technical advantages, related to the predictability of the blood supply.